2018
DOI: 10.1089/humc.2017.142
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Osteoarthritis: Pharmacokinetics of Intra-Articular Self-Complementary Adeno-Associated Virus Interleukin-1 Receptor Antagonist Delivery in an Equine Model

Abstract: Toward the treatment of osteoarthritis (OA), the authors have been investigating self-complementary adeno-associated virus (scAAV) for intra-articular delivery of therapeutic gene products. As OA frequently affects weight-bearing joints, pharmacokinetic studies of scAAV gene delivery were performed in the joints of the equine forelimb to identify parameters relevant to clinical translation in humans. Using interleukin-1 receptor antagonist (IL-1Ra) as a secreted therapeutic reporter, scAAV vector plasmids cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 67 publications
6
59
0
Order By: Relevance
“…Safety is an overriding concern when using gene therapy for nonlethal diseases such as OA. Several detailed studies, the present one included, have demonstrated no evidence of persistent viral genomes outside the injected joint, and no major adverse events have been reported , thus providing reassurance on this issue.…”
Section: Il‐1ra Cdna Delivery In Animal Models Of Osteoarthritissupporting
confidence: 58%
See 1 more Smart Citation
“…Safety is an overriding concern when using gene therapy for nonlethal diseases such as OA. Several detailed studies, the present one included, have demonstrated no evidence of persistent viral genomes outside the injected joint, and no major adverse events have been reported , thus providing reassurance on this issue.…”
Section: Il‐1ra Cdna Delivery In Animal Models Of Osteoarthritissupporting
confidence: 58%
“…Detailed in vitro studies by Bajpayee and colleagues have shown that particles larger than ~10 nm, depending on shape and charge, do not penetrate the extracellular matrix of normal cartilage. However, AAV, which is ~20 nm in size, is able to transduce chondrocytes in situ after injection into equine joints . This may be enabled by the pumping action that occurs in cartilage as the horse moves.…”
Section: Il‐1ra Cdna Delivery In Animal Models Of Osteoarthritismentioning
confidence: 99%
“…The recombinant AAV (rAAV) DNA is expressed and incorporated into the viral vector capsule using a plasmid system in a packaging cell line 12 . There are many serotypes of AAV and appropriate rAAV vectors are chosen for specific applications based on tissue tropism and transduction efficiency 13–16 . In horses, rAAVs have predominantly been used for intra‐articular delivery of anti‐inflammatory or anabolic genes such as IL1‐RA, 14,15,17,18 IGF‐1, 19,20 and most recently, IL‐10 21 …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, IL-1β production is associated with cartilage degeneration in OA (20), and it was shown that inflammatory molecules produced by synovium can induce ECM loss (21). The importance of IL-1 signaling was also highlighted in animal models of posttraumatic OA (2224). Potential clinical relevance of identified translationally controlled targets, such as Fn1 and an orphan receptor Nr4a1, was tested in diseased cartilage and in a rat model of post-traumatic OA.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications from two independent groups have highlighted the importance of IL-1 signaling in various small and larger animal models of posttraumatic OA (2225). For example, IL-1 receptor antagonist therapy significantly improved cartilage, synovial membrane parameters, and disease-modifying effects in the equine OA model (26).…”
Section: Introductionmentioning
confidence: 99%